Cleaner production of baicalein by novel high-temperature-little-acid hydrolysis of baicalin - Lingling Tang; Jiali Shao; Hanxue Zheng; Jixuan Chen; Guohua Xia; Huan Yang; Yaya Yang; Yuping Shen (Green Chemistry Letters and Reviews, 2024)
Baicalein, usually obtained after the removal of 7-O-β-D-glucuronic acid from baicalin, has strong pharmacological activity. In this study, a novel strategy for efficient and eco-friendly preparation of baicalein was established by high-temperature-little-acid hydrolysis of baicalin. The effects of inorganic acids, solvents, solid–liquid ratio, HCl concentration and hydrolysis duration on the yield of baicalein were investigated by one-factor-at-a-time experiment. Then, an orthogonal experiment design was conducted for the optimal hydrolysis conditions, namely, baicalin was boiled in n-BuOH solution containing 0.50% HCl (w/v) at 130°C for 2.0 h with solid–liquid ratio at 1:25 (g/mL). In the 60-fold scale-up experiment, the yield of baicalein was achieved at 83.5% ± 6.3%, and its purity was increased from 74.2% to 98.7% after purification. Compared with reported methods, acid consumption per unit product of the newly developed strategy was approximately 80 times lower than that of conventional acid hydrolysis, and time consumption was substantially reduced. Overall, the novel strategy showed great prospects for a cleaner large-scale production of baicalein, which provides a new alternative desirable for the preparation of natural products with high efficiency and low consumption in the pharmaceutical industry.